KEPUASAN KONSUMEN DALAM MEMEDIASI KUALITAS PELAYANAN DAN LOKASI TERHADAP LOYALITAS KONSUMEN PADA AKBAR FUTSAL SITUBONDO - Zarkasih, Ahmad Catur; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2023)
Marketing activities are actions taken by companies with the aim of communicating and offering goods or services to consumers. The company's success in achieving its targets is largely determined by an effective marketing strategy. this study aims to analyze and examine the impact of service quality, location, and consumer satisfaction on consumer loyalty at Akbar Futsal Situbondo. This study used a simple random sampling technique in taking the sample. The collected data were analyzed and the hypotheses were tested through the Structural Equation Model - Partial Least Square (PLS-SEM) approach. Based on the results of testing the hypothesis using the Smart PLS 3.0 application, it was found that there is a positive and significant influence between service quality and location on customer satisfaction. In addition, service quality and location also have a positive and significant effect on consumer loyalty. Apart from the direct effect, there is also an indirect effect between service quality and location on consumer loyalty through consumer satisfaction. The indirect effect of service quality on customer loyalty through customer satisfaction has a positive and significant effect, while the indirect effect of Location on consumer loyalty through customer satisfaction also has a positive effect, but it is not statistically significant.